2014
DOI: 10.1002/qj.2470
|View full text |Cite
|
Sign up to set email alerts
|

Observation impact over the southern polar area during the Concordiasi field campaign

Abstract: The impact of observations on analysis uncertainty and forecast performance was investigated for austral spring 2010 over the southern polar area for four different systems (NRL, GMAO, ECMWF and Météo-France) at the time of the Concordiasi field experiment. The largest multi-model variance in 500 hPa height analyses is found in the southern sub-Antarctic oceanic region, where there are rapidly evolving weather systems, rapid forecast-error growth, and fewer upper-air wind observation data to constrain the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
(35 reference statements)
2
24
0
Order By: Relevance
“…With improved technology and power systems, the barrier is becoming more of a financial one than a logistical one: improved observations of the polar regions are possible, but are they worth the cost? To answer this, observing system experiments (OSEs) are required [see, e.g., Boullot et al (2016)], in which specific observations are withheld (denied) during the data assimilation process, with a particular focus on user requirements for these regions. To carry out these experiments, a sustained observing period is required with significantly enhanced spatial and temporal coverage-a Year of Polar Prediction (see below).…”
Section: How To Improve Polar Prediction Capacity?mentioning
confidence: 99%
“…With improved technology and power systems, the barrier is becoming more of a financial one than a logistical one: improved observations of the polar regions are possible, but are they worth the cost? To answer this, observing system experiments (OSEs) are required [see, e.g., Boullot et al (2016)], in which specific observations are withheld (denied) during the data assimilation process, with a particular focus on user requirements for these regions. To carry out these experiments, a sustained observing period is required with significantly enhanced spatial and temporal coverage-a Year of Polar Prediction (see below).…”
Section: How To Improve Polar Prediction Capacity?mentioning
confidence: 99%
“…The predictive skill when integrated over Southern Hemisphere is largely driven by a latitude band of very high synoptic activity located over the southern oceans near 50∘S. This is an area where analysis increments are large, indicating significant and fast growing model errors (Boullot et al , ). The daily variability of predictive skill is substantial for both poles (not shown) and the seasonal skill cycle is most pronounced for the South Pole, where the errors are lowest during Southern Hemisphere summer.…”
Section: Predictive Skillmentioning
confidence: 99%
“…Wei et al () and Boullot et al () have identified significant differences between global NWP model analyses in terms of both mean analysis state and so‐called analysis activity, which is the variability of the analysis anomalies calculated from the difference between daily analyses and the analysis climate. Mean state and variability have clear implications for both forecast initialization and verification.…”
Section: Analysis Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, observations from passive and active microwave instruments and infrared spectrometers, and analysis techniques that promise better sensing of the shallow lower polar troposphere, are important . Also here, much can be gained from assessing reanalyses and observational campaigns targeting the poles such as Concordiasi (Boullot et al, 2016).…”
Section: P Bauer and T Jungmentioning
confidence: 99%